World federation of pediatric intensive care and critical care societies: Global sepsis initiative - Kissoon, N.; Carcillo, J.; Espinosa, V.; Argent, A.; Devictor, D.; Madden, M.; Singhi, S.; Van Der Voort, E.; Latour, Jos (2011)
Background: According to World Health Organization estimates, sepsis accounts for 60%-80% of lost lives per year in childhood. Measures appropriate for resource-scarce and resource- abundant settings alike can reduce sepsis deaths. In this regard, the World Federation of Pediatric Intensive Care and Critical Care Societies Board of Directors announces the Global Pediatric Sepsis Initiative, a quality improvement program designed to improve quality of care for children with sepsis. Objectives: To announce the global sepsis initiative; to justify some of the bundles that are included; and to show some preliminary data and encourage participation. Methods: The Global Pediatric Sepsis Initiative is developed as a Web-based education, demonstration, and pyramid bundles/ checklist tool (http://www.pediatricsepsis.org or http://www. wfpiccs.org). Four health resource categories are included. Category A involves a nonindustrialized setting with mortality rate <5 yrs and >30 of 1,000 children. Category B involves a nonindustrialized setting with mortality rate <5 yrs and <30 of 1,000 children. Category C involves a developing industrialized nation. In category D, developed industrialized nation are determined and separate accompanying administrative and clinical parameters bundles or checklist quality improvement recommendations are provided, requiring greater resources and tasks as resource allocation increased from groups A to D, respectively.Results: In the vanguard phase, data for 361 children (category A, n = 34; category B, n = 12; category C, n = 84; category D, n = 231) were successfully entered, and quality-assurance reports were sent to the 23 participating international centers. Analysis of bundles for categories C and D showed that reduction in mortality was associated with compliance with the resuscitation (odds ratio, 0.369; 95% confidence interval, 0.188-0.724; p < .0004) and intensive care unit management (odds ratio, 0.277; 95% confidence interval, 0.096-0.80) bundles. Conclusions: The World Federation of Pediatric Intensive Care and Critical Care Societies Global Pediatric Sepsis Initiative is online. Success in reducing pediatric mortality and morbidity, evaluated yearly as a measure of global child health care quality improvement, requires ongoing active recruitment of international participant centers.